Greco-Roman cities at the crossroads of cultures the 20th anniversary of Polish-Egyptian conservation mission Marina El-Alamein - Bąkowska-Czerner, Grażyna 1968-; Czerner, Rafał 1958- (Archaeopress archaeology, 2019)
These papers present research from different regions ranging from ancient Mauritania, through Africa, Egypt, Cyprus, Palestine, Syria, as well as sites in Crimea and Georgia. Topics include: topography, architecture, interiors and décor, religious syncretism, the importance of ancient texts, pottery studies and conservation